Poorly differentiated carcinoma of the rectum with aberrant immunophenotype: A case report - Giannopoulos, A (Baishideng Publishing Group Co., Limited, 2007)
We report a case of a poorly differentiated epithelial tumour of the rectum with a highly pleomorphic morphology and an aberrant immunophenotype, including the expression of epithelial markers, the focal parameter of neuroendocrine differentiation, and the unexpected detection of CD-117 overexpression. A 69-year-old man was admitted to our clinic complaining of rectal bleeding and weight loss. Colonoscopy showed an ulcerative bleeding mass located about 8 cm from the anal verge. Abdominal and pelvis CT scans demonstrated a large low-density lesion with extracanalicular growth from the middle rectum, with local lymph-node spread, and without tumour infiltration of other pelvic organs, or evidence of distant intra-abdominal spread. The patient underwent a low anterior resection for rectal cancer together with wide resection of lymph nodes. In immunohistochemical analysis, pankeratin and Epithelial Membrane Antigen (EMA) immunolabeling proved the epithelial nature of the tumor cells. Chromogranin A and Leukocyte Common Antigen (LCA) were negative, whereas CD-56 expression was scanty and Neuron Specific Enolase (NSA) was heavily and diffusely expressed. Ki67 immunoexpression was particularly increased. Interestingly, the intense c-kit immunoreactivity (100%) was a common feature. The above phenotypic and immunohistochemical profile was consistent with an anaplastic carcinoma of the large intestine, with focal neuroendocrine differentiation and diffuse immunoreactivity to c-kit protein. Given the resistance of this tumor to conventional chemotherapy and radiation, the incidence of the c-kit alteration may represent a novel approach to a gene-directed treatment using a c-kit inhibitor (STI571) similar to that which has been proposed in GISTs.